METHODOLOGY FOR TEACHING FUTURE COMPUTER TEACHERS OPERATING SYSTEMS USING A VIRTUAL ENVIRONMENT - Koshanova, Г.Д.; Koshanova, М.Д.; Talipov, Д.Р. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
At present, one of the key challenges in the higher education system is the preparation of competitive and professionally competent informatics teachers. This article provides a theoretical and practical justification for the importance of using virtual machines in teaching operating systems to future informatics teachers. The aim of the study is to develop an effective methodology for teaching operating systems through the use of virtual machines. The article examines the capabilities of virtualization tools such as VirtualBox and describes ways to apply them effectively in the educational process. Practical tasks performed in a virtual environment enable students to safely and flexibly develop skills in operating system management. In addition, the proposed methodology contributes to the optimal use of hardware resources and increases the efficiency of working with complex software. As a result of the study, practical tasks for future informatics teachers were developed and integrated into the educational process. In conclusion, virtualization technologies are proposed as an effective tool for developing students’ practical competencies.